Will Urban Agriculture rescue the current cities? - Branduini, Paola (Steiner, 2019)
Although the evident social benefits of Urban Agriculture (UA), the process of UA recognition by local administrations took a long time. For this reason, the example of the city of Milan is quite significant. Milan recently gained a lot of fame as one the most advanced cities in food policy promotion: it encouraged and opened to signature the world Urban Food Policy Pact in 2015 and gained the Guangzhou International Award in 2018 for best urban policy. Nevertheless, the recognition of UA values by the Municipality of Milan and regional institutions took a long way.
Keywords: Stadtraum; Landwirtschaft; Lebensmittelproduktion; Nachhaltige Stadtentwicklung; Entwicklungsperspektive; Großstadt; Fallbeispiel